A formação em educação ambiental e as ações socioambientais dos bolsistas Pibid/ Unesp na educação pública paulista - Ferreira, Aline Veríssimo [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Este estudo concebe a Educação Ambiental como um elemento de transformação social contribuindo para o enfrentamento da crise socioambiental resultante da atual organização social da humanidade. Partindo desses pressupostos, consideramos relacionar dois aspectos que estão ligados ao trabalho educativo na educação escolar: a formação de professores e a Educação Ambiental. Neste sentido, tomamos referência do processo de formação inicial os estudantes dos cursos de licenciatura que atuam como bolsistas no Programa Institucional de Bolsa de Iniciação à Docência (PIBID) da Universidade Estadual Paulista (UNESP). Assim, este trabalho propõe identificar e compreender as ações socioambientais desenvolvidas nas escolas pelos bolsistas do programa PIBID. Para atingir o objetivo buscamos elementos da Educação Ambiental crítica e da Pedagogia Histórico Crítica. Como procedimentos de pesquisa utilizamos o recurso do questionário que possibilitou dados quantitativos e qualitativos, os dados qualitativos serão analisados com base na Análise de Conteúdo (BARDIN, 1977). Os dados obtidos possibilitaram compreender que 52% dos sujeitos participantes da pesquisa afirmaram desenvolver atividades sobre Educação Ambiental na atuação no programa. Identificamos que as diferentes concepções sobre Educação Ambiental e ações socioambientais apresentaram ser conservacionistas e, revelam fragilidades na formação inicial quanto à apropriação da Educação Ambiental crítica. Segundo os referenciais críticos da Educação Ambiental, concepções conservacionistas refletem na atuação do professor e fragiliza as possibilidades de um ambiente pedagógico na perspectiva crítica da Educação Ambiental. Este trabalho pretende contribuir para a reflexão das ações e concepções desenvolvidas no Pibid e produzir conhecimentos que contribuam para a reflexão da inclusão das ações socioambientais nas diferentes licenciaturas na perspectiva da Educação Ambiental Crítica.

This study conceives of Environmental Education as an element of social transformation to face the socio-environmental crisis resulting from the current social organization of humanity. Starting from the assumptions, we consider to relate two aspects that are so related to the educational work in school education: a teacher training and an Environmental Education. In this sense, we have taken references to the initial training process of labor scholarship studies, such as the São Paulo State University (UNESP) Scholarship Initiation Program (PIBID). Thus, this work proposes to identify and visualize as socio-environmental actions developed in the schools by the PIBID scholarship recipients. For more information on the subject, click here for more information on the subject, please click here for more information on the subject. Get detailed and qualitative information, qualitative and physical data. Content Analysis (BARDIN, 1977). The data obtained enabled 52% of the subjects participating in the research on the activity of development of activities on Environmental Education to work without a program. We identified as different conceptualizations on Environmental education and social and environmental actions that presented conservatives and reveal weaknesses in the initial formation regarding the environment of Critical Environmental Education. According to the critical references of Environmental Education, conservationist conceptions reflect on the teacher's performance and weakens as possibilities of a pedagogical environment in the critical opinion of Environmental Education. This paper aims to contribute to a reflection of the actions and concepts developed not Pibid and is published to contribute to the reflection of the inclusion of social and environmental actions in the different licenses from the perspective of Critical Environmental Education.
The training in environmental education and the socio-environmental actions of the Pibid / Unesp scholarship holders in the public education of São Paulo
Keywords: Ações socioambientais; Educação ambiental; Formação de professores; Pibid; Socio-environmental actions; Environmental education; Teacher training